The Amount of Hepatocyte Turnover That Occurred during Resolution of Transient Hepadnavirus Infections Was Lower When Virus Replication Was Inhibited with Entecavir - Mason, William S. (American Society for Microbiology (ASM), 2009)
Transient hepadnavirus infections can involve spread of virus to the entire hepatocyte population. In this situation hepatocytes present following recovery are derived from infected hepatocytes. During virus clearance antiviral cytokines are thought to block virus replication and formation of new covalently closed circular DNA (cccDNA), the viral transcriptional template. It remains unclear if existing cccDNA is eliminated noncytolytically or if hepatocyte death and proliferation, to compensate for killing of some of the infected hepatocytes, are needed to remove cccDNA from surviving infected hepatocytes. Interpreting the relationship between hepatocyte death and cccDNA elimination requires knowing both the amount of hepatocyte turnover and whether cccDNA synthesis is effectively blocked during the period of immune destruction of infected hepatocytes. We have addressed these questions by asking if treatment of woodchucks with the nucleoside analog inhibitor of viral DNA synthesis entecavir (ETV) reduced hepatocyte turnover during clearance of transient woodchuck hepatitis virus (WHV) infections. To estimate hepatocyte turnover, complexity analysis was carried out on virus-cell DNA junctions created by integration of WHV and present following recovery in the livers of WHV-infected control or ETV-treated woodchucks. We estimated that, on average, 2.2 to 4.8 times less hepatocyte turnover occurred during immune clearance in the ETV-treated woodchucks. Computer modeling of the complexity data suggests that mechanisms in addition to hepatocyte death were responsible for elimination of cccDNA during recovery from transient infections.